Induction of Labor: A Comparative Study of Intravaginal Misoprostol and Dinoprostone - Aqueela Ayaz (Elsevier, 2010)
Objective: To compare the efficacy and safety of intravaginal misoprostol and dinoprostone for elective induction of labor in nulliparous women with an unfavorable cervix. Materials and Methods: A quasi-experimental study was conducted in Bahawal Victoria Hospital, Bahawalpur, Pakistan, from July 1, 2005 to August 31, 2006. A total of 120 primigravid women with gestational ages of > 40 weeks to < 42 weeks were divided into two groups. Group A (n = 60) was given 50 μg of misoprostol and Group B (n = 60) was given 3 mg of dinoprostone every 6 hours, for a maximum of three doses. Results: The induction to onset of significant uterine contractions and delivery intervals were lower in Group A than in Group B (6.1 vs. 7.2 hours; p = 0.16; and 8.2 vs. 11.0 hours; p = 0.007, respectively). Group A had a lower cesarean section rate than Group B (7% vs. 30%; p = 0.003), but a higher rate of uterine hyperstimulation (10% vs. 3%; p = 0.16), tachysystole (17% vs. 3%; p = 0.02), and neonatal admissions to the intensive care unit within 24 hours of delivery (4 vs. 3; p = 0.71) and after 24 hours (2 vs. 1; p = 0.56) than Group B. Conclusion: Vaginal misoprostol is more effective than dinoprostone for the elective induction of labor beyond 40 weeks of gestation, but is associated with more uterine hyperstimulation, tachysystole, and neonatal intensive care unit admissions.